Evaluation of 2017 Secondary School Information Technologies and Software Course Curriculum According to Teacher and Student Views - Kuzu Demir, Elif Buğra; GÜNDÜZ, GÜLTEN FERYAL (My University, 2019)
In the information age we are in, the constant change, update and increase of information has led to changes in the way that information is obtained by individuals and in occupations that are in demand and this situation increased the importance of information technologies. The name of the computer lesson which was started to be taught in high schools in mid-1980’s was changed and it began to be taught as a subject in lower levels of education in Turkey. Taking into account the 21st century learning skills, it is inevitable to teach information technologies and skills at all levels of education starting from preschool period. Changes have been made in the scope, name and compulsory I elective courses of the computer course curriculum (MEB ÎGM, 1998) taught as an elective course in secondary schools since 1998- 1999 academic year. Information Technology and Software (ITS) course curriculum was last changed in 2017; the altered curriculum of this course, which is compulsory in the 5th and 6th grades of secondary school, has been gradually implemented since the 2017-2018 academic year. Program evaluation is the last step of program development and the element required to make a decision about the effectiveness, efficiency and usefulness of a developed program by considering certain criteria. The findings of the evaluation of a program provide guidance to educators and decision-makers on the termination, continuation or correction of the program. Although there are studies on the evaluation of secondary school information technologies and software course curriculum in previous years (Durdukoca & Arıbaş, 2011; Erçetin & Durak, 2017; Uzgur & Aykaç, 2016; Akbıyık & Seferoğlu, 2012; Baran, Akpınar, Karakoyun & Koca, 2016; Çengel) Karakuş, Çimen Çoşğun & Lal, 2015); there are only a few studies in the field that evaluate the version of the 2017 ITS draft curriculum before implementation (Information Technology Educators Association, 2017; Gündüz & Kuzu Demir, 2018; Mercimek & îliç, 2017). In this respect, this study is one of the first comprehensive studies to evaluate the 2017 ITS program after its implementation. Based on these problems and necessities, the general purpose of this study is to evaluate the 2017 BTY curriculum according to the views of teachers and students. For this general purpose, answers for the following questions were sought. 1) According to the opinions of the teachers who took 5th grade ITS course, what is the level of reaching the criteria foreseen for the; 1.1. Acquisitions 1.2. Content 1.3. Teaching-learning process 1.4. Evaluation 2) According to the opinions of the 5th grade students, what is the level of reaching the criteria foreseen for the; 1.2. Acquisitions 1.2. Content 1.3. Teaching-learning process 1.4. Evaluation 3) Do the students’ opinions about ICT course curriculum differ according to their gender and level of computer use? Method There are many types of program evaluation according to the philosophy, purpose, target group and measurement tools used in the evaluation. In this research, the discrepancy model of Provus which is one of the goal-based program evaluation models was used as the program evaluation model. In this model, an educational program is analysed according to the differences between standards, expectations and achievements within the dimensions of objectives, content, methods and evaluation and program is determined the as a result of the obtained findings (Worthen & Sanders, 1987). In order to have a holistic perspective on the evaluation of the ITS curriculum, this study will utilize mixed methods sequential exploratory design. According to Creswell (2003), the mixed methods sequential exploratory design consists of two stages. In the first stage, the quantitative data that are prioritized in the study are collected and analyzed. In the light of thefindings, the second stage, qualitative data collection is started in order to explain deeply the quantitative data obtained from the first stage (Creswell, 2014; Creswell & Plano, 2007). The study aimed to evaluate the curriculum of 2017 IT course with a holistic approach by the help of the views of students and teachers on the curriculum of 2017 IT course. Within this context, the research population of the study was determined as the fifth grade students, and the IT teachers in the secondary schools located in central districts of Eskişehir. Accordingly, the sampling method differed with regard to the characteristics of the participants. The students were selected through a cluster sampling method. The data from the 815 students (female=409, male=395) were collected through a single factor valid and reliable scale developed by the researcher, which explains a percentage of 39,917% of the total variance with a high internal consistency. A questionnaire developed by the researchers was fulfilled by 39 teachers. The data were analysed through both descriptive and inferential statistics with the help of SPSS 22.0 package programme. Obtained Results The findings showed that the views of the students related to the evaluation of 2017 ITS curriculum was significantly positive, which significantly differed with level of use but not with gender. As for the students’ scale, the highest mean score of an item is 4,20, which the students mentioned that what they had learned in the course provided them to use IT effectively and correctly. Another item is “What I have learned in the course provides me to use visual expressions (schemes, arrows, etc.) step-by-step while writing a computer program”, which had a considerably high mean score of 4.19. The lowest mean scores of two items were respectively 3,72 and 3,82, which the students mentioned that the course activities were related to their daily life and what they had learned in the course develops their skills in expressing themselves in their mother tongue. Findings also revealed that the views of the teachers related to the evaluation of 2017 ITS curriculum is significantly positive as well, which significantly did not differ with gender, level of education, period of service but differed with the satisfactory level of mandatory and voluntary in-service training. Teachers who mentioned that the in-service training given to the teachers both for mandatory and voluntarily were satisfactory had more positive views related to the evaluation of 2017 ITS curriculum. As for the students’ scale, the highest mean score of an item is 4,54, which the teachers expressed that the 2017 ITS curriculum improved their students’ research skills. Other items which had considerably high mean scores of 4.33 were “The curriculum develops students' information technology and software skills” and “The curriculum develops students'computational thinking skills”. The lowest mean scores of two items were respectively 3,21 and 3,34, which the teachers indicated that the time allocated to the Digital Product Creation and Computational Thinking units in the program were sufficient.
Keywords: 2017 Information Technologies and Software Course Curriculum; Secondary School 5th Grade Students; ITS Teachers; Program Evaluation; Provus’ Discrepancy Model